Communication—Potential of the π-Gate InAs HEMTs for High-Speed and Low-Power Logic Applications. (1st January 2019) - Yao, Jing-Neng; Lin, Yueh-Chin; Wong, Ying-Chieh; Huang, Ting-Jui; Hsu, Heng-Tung; Sze, Simon M.; Chang, Edward Yi
Abstract : Composite channel (In0.65 Ga0.35 As/InAs/ In0.65 Ga0.35 As) high electron mobility transistors (HEMTs) with π-gate structure were investigated for high-speed and low-power logic applications. The conventional and tri-gate MESA HEMTs were compared with the π-gate device for evaluation. The π-gate device exhibited the best maximum transconductance value of 1584 mS/mm, on-state current of 332mA/mm, subthreshold swing (SS) of 78.1 mV/decade, and ION /IOFF ratio of 3 × 10 4 at VDS = 0.5 V at room temperature. These results indicated that the designed π-gate InAs devices improve the electrical characteristics of InAs HEMTs for high-speed and low-power logic applications.